Correlation analysis of fluctuations in the serum interleukin-38, soluble RAGE and FIAF levels in prognosis of chronic obstructive pulmonary disease (COPD): Serum interleukin-38, soluble RAGE and FIAF levels in prognosis of COPD - Fu, Lu; Dou, Juanli; Ren, Boyu; Wang , Jing; Liu, Cong; Li, Binfeng (Journal of Medical Biochemistry, 2026)
[Objective] To explore the changes in the serum interleukin-38, soluble receptor for advanced glycation end products (soluble RAGE) and Fasting-Induced Adipose Factor (FIAF) levels in patients with chronic obstructive pulmonary disease (COPD) and to analyze their relationships with the severity and prognosis of the disease. [Methods] A total of 272 COPD patients admitted to the hospital from May 2023 to March 2025 were selected as the case group. Based on how quickly the condition progressed, the patients were split into two groups: those in the acute exacerbation stage (n=158) and those in the stable stage (n=114). An additional 176 healthy individuals who went to the hospital at that time for a physical checkup made up the control group. Serum FIAF, TLR4, soluble RAGE, and interleukin-38 levels were examined for each group, and the relationships between the above indicators and the severity and prognosis of the disease were analyzed. [Results] While soluble RAGE was lower in the acute exacerbation group than in the stable and control groups (P<0.05), serum levels of FIAF, TLR4, and interleukin-38 were greater in the acute exacerbation group than in the stable and control groups. In the case group, patients with Grade III-IV disease had higher serum levels of FIAF, TLR4, and interleukin-38 than patients with Grade I-II disease, whereas soluble RAGE levels were lower than those of Grade I-II disease patients (P<0.05). While soluble RAGE levels were lower in the nonsurviving group than in the surviving group (P<0.05). The nonsurviving group had higher levels of serum FIAF, TLR4, and interleukin-38 than the surviving group. The area under the curve for the combined prediction of the prognosis of COPD patients by interleukin-38, soluble RAGE, TLR4, and FIAF was 0.955, according to receiver operating characteristic curve analysis, which was greater than that for interleukin-38 (0.738), soluble RAGE (0.815), TLR4 (0.786), and FIAF (0.763). Binary logistic analysis was performed according to the following GOLD classification: Acute Physiology and Chronic Health Evaluation II (APACHE II) score; interleukin-38 expression >61.55ng/L; soluble RAGE expression ≤272.72 ng/L; TLR4 expression >4.27 ng/mL; and FIAF expression > 1,172.53 ng/L, which are separate risk factors influencing COPD patients’ prognosis. [Conclusion] Serum interleukin-38, soluble RAGE, TLR4 and FIAF levels in patients with COPD can reflect disease progression and can be used for prognosis assessment.